Contemporary Difficulties with ?Identity? - Tańczuk, Renata (INSTED: Interdisciplinary Studies in Education & Society, 1998)
Identity is one of the most popular categories in modem human sciences. This popularity results from, among other things, perceiving the difficulties in self-defining that the modern man may have. There are also various problems connected with modern understanding of identity. Thus, the discussion on identity is lead in two different dimensions. The first one is concerned with the causes of difficulties in self-defining and the other one deals with contemporary notions of identity. The author ponders over the understanding of identity developed by symbolic interactionism and over Derridian philosophy consequences to the reflection, presented by E. E. Sampson. She also uses Ch. Taylor's conception to reveal some characteristics of personal identity.